Surface-nitrided seawater-corrosion-resistant wave-absorbing material and preparation method thereof

By pretreating carbonyl iron powder, surface nitriding and heat treatment, the iron nitride protective layer is formed, which solves its corrosion problem in seawater environment, improves corrosion resistance and electromagnetic properties, and reduces production costs.

CN119542766APending Publication Date: 2025-02-28XIAN AERONAUTICAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411915628.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Carbonyl iron powder is prone to corrosion in salt-containing environments such as seawater, resulting in a decrease in absorbing performance and release of harmful corrosion products. The corrosion resistance of the prior art is limited and the production cost is high.

Method used

By pretreating carbonyl iron powder, surface nitriding and heat treatment, a dense iron nitride protective layer is formed to enhance its corrosion resistance in the marine environment.

Benefits of technology

It significantly improves the corrosion resistance and electromagnetic properties of carbonyl iron powder, extends its service life, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542766A_ABST
    Figure CN119542766A_ABST
Patent Text Reader

Abstract

The invention provides a surface nitriding treatment seawater corrosion-resistant wave-absorbing material and a preparation method thereof, and belongs to the technical field of metal surface treatment.The preparation method specifically comprises the steps that firstly, carbonyl iron powder is pretreated, specifically, acid pickling is conducted to remove surface impurities and an oxide layer, and then the carbonyl iron powder is subjected to surface nitriding treatment; and cleaning residual acid liquor and other soluble impurities with water. And then the pretreated carbonyl iron powder is placed in a nitriding furnace to be subjected to surface nitriding treatment, and after nitriding treatment is completed, heat treatment and surface modification treatment are conducted. And complicated chemical reaction and high-temperature treatment are abandoned, so that the production cost is reduced. After nitriding treatment, a compact iron nitride protection layer is formed on the surface of the carbonyl iron powder, so that the corrosion resistance of the carbonyl iron powder material in a marine environment is enhanced, the electromagnetic property of the carbonyl iron powder material is optimized, and the thermal stability and the electromagnetic wave absorption efficiency are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal surface treatment, and particularly relates to a seawater corrosion-resistant absorbing material with surface nitridation treatment and a preparation method thereof. Background Art

[0002] With the rapid development of science and technology, especially the widespread application of electronic equipment, communication technology and military technology, in the military field, stealth technology is of great significance for improving the survivability and penetration capability of weapons and equipment. An important aspect of stealth technology is to reduce the radar reflection cross section of weapons and equipment by coating them with absorbing materials, thereby reducing the probability of being detected by enemy radar. Therefore, absorbing materials play an important role in military stealth technology.

[0003] Carbonyl Iron Powder (CIP), as an important magnetic material, has a wide range of applications in the field of microwave absorbing materials. Carbonyl iron powder has the characteristics of high saturation magnetization, high magnetic permeability, low production cost and good temperature stability, which makes it play an important role in electromagnetic wave absorbers. Carbonyl iron powder is obtained by decomposing pentacarbonyl iron (Fe(CO)5) under heating conditions. It usually appears as a powder with an onion-shaped structure, and its main chemical component is iron. In the application of microwave absorbing materials, carbonyl iron powder is widely used in stealth equipment due to its excellent microwave absorbing performance. In order to further improve the microwave absorbing performance of carbonyl iron powder, researchers have adopted a variety of modification methods, including morphology modification, coating modification, and composite modification. These modification methods are aimed at improving the dielectric properties and magnetic properties of carbonyl iron powder, so as to achieve more efficient microwave absorption. For example, by coating SiO2 on the surface of carbonyl iron powder, its dielectric constant can be reduced, the impedance matching characteristics can be improved, and the microwave absorbing performance can be improved. In addition, compounding carbonyl iron powder with carbon materials, such as graphene and carbon nanotubes, can further improve the wave absorption performance, broaden the absorption band, and reduce the density of the material. Its excellent magnetic properties and wave absorption performance, as well as its electromagnetic compatibility and stealth capabilities in modern electronic equipment and military equipment can be further improved through modification. With the advancement of materials science, the research and application prospects of carbonyl iron powder and its composite materials are very broad.

[0004] However, carbonyl iron powder is prone to corrosion in salty environments such as seawater. In seawater, due to the presence of a large amount of electrolytes and oxygen, a series of complex electrochemical reactions will form on the surface of the iron powder, leading to accelerated corrosion. These reactions include the oxidation of iron, the generation of hydroxide ions, and the final formation of rust (Fe2O3·nH2O). The corrosion of carbonyl iron powder will not only lead to a decrease in the material's wave absorption performance, but may also release harmful corrosion products and pollute the environment. In order to improve the corrosion resistance of iron powder, researchers have adopted a variety of methods, such as coating the surface of iron powder with a protective layer such as aluminum oxide (Al2O3) or silicon dioxide (SiO2) by atomic layer deposition technology to improve its corrosion resistance, but it also brings some problems, such as increased cost, changes in dielectric properties, changes in magnetic permeability, changes in thermal stability, limited corrosion resistance, environmental adaptability, complexity of processing and potential environmental impact. In general, the corrosion of carbonyl iron powder in seawater is a complex process involving a variety of physical and chemical factors. Through surface modification and coating technology, its corrosion resistance can be effectively improved and its service life can be extended.

[0005] In the prior art, in the "Anti-rust carbonyl iron powder absorbing material and its preparation method" disclosed in Chinese invention patent publication number CN113388231A, carbonyl iron powder and acetone are mixed and stirred to obtain a first mixture, and ammonia water, tetraethyl orthosilicate and titanate coupling agent are added to obtain a second mixture, and corrosion-resistant carbonyl iron powder is obtained after hydrothermal treatment. However, this method has high cost and complex process, and is not suitable for large-scale application in seawater environment. In the "Preparation method of aluminum phosphate coated carbonyl iron antioxidant absorbing material" disclosed in Chinese invention patent publication number CN107253738B, a phosphate suspension is poured into a precursor carbonyl iron suspension solution, mixed and stirred to react, and washed and separated, and the sample is calcined at high temperature under inert atmosphere conditions to obtain an aluminum phosphate coated carbonyl iron (Fe@AlPO4) composite material. However, this method has limited corrosion resistance and is not suitable for the use of absorbing materials in seawater environments for a long time. It involves ultrasound, mixing, drying, calcination and other steps, which require precise control to ensure the uniformity and quality of the coating layer, increase production costs and complexity, and lead to a narrowing of the effective absorption area of ​​the material and changes in reflection loss performance. It can be seen that the existing technology still has problems such as failure to provide continuous protection, high production costs, difficulty in mass production, and serious material performance loss. Summary of the invention

[0006] The purpose of the embodiments of the present invention is to provide a surface nitrided seawater corrosion-resistant absorbing material and a preparation method thereof, so as to achieve long-term stability and corrosion resistance of carbonyl iron powder in a marine environment, while ensuring that the carbonyl iron powder has good electromagnetic wave absorption performance.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is a method for preparing a seawater corrosion-resistant absorbing material with surface nitridation treatment, and the specific steps are as follows: S1. Pre-treating the carbonyl iron powder, including pickling and water washing; S2, performing surface nitriding treatment on the pretreated carbonyl iron powder; S3. heat treating and surface modifying the carbonyl iron powder after nitriding.

[0008] Furthermore, the specific steps of S1 are: S101. Soak carbonyl iron powder with an average particle size of 20-50 μm in a dilute hydrochloric acid or dilute sulfuric acid solution with a mass concentration of 8%-10% for 5-10 minutes; then wash with deionized water for 3-4 times, each time for 2-3 minutes; S102, drying the cleaned carbonyl iron powder at 80-100°C for 30-45 min.

[0009] Furthermore, the specific process of S2 is: continuously filling the nitriding furnace with nitriding gas until the furnace body is full, and then spreading the carbonyl iron powder treated by S1 into the nitriding furnace for nitriding at 400-600°C for 4-8 hours; and then naturally cooling to room temperature.

[0010] Furthermore, the nitriding gas is one of nitrogen or ammonia.

[0011] Furthermore, the heat treatment in S3 is specifically heat treatment at 80-100° C. for 1-2 h in a vacuum drying oven with a vacuum degree not higher than -0.1 MPa.

[0012] Furthermore, the specific process of surface modification in S3 is: adding the heat-treated nitrided carbonyl iron powder to a polyvinyl pyrrolidone aqueous solution, ultrasonically oscillating for 0.4 to 0.6 hours, adding aniline monomer, stirring with a glass rod for 10 to 12 minutes, and then magnetically stirring the solution in an ice bath for 2 to 3 hours; finally, washing with anhydrous ethanol and deionized water for 2 to 3 times respectively.

[0013] Furthermore, the mass ratio of the nitrided carbonyl iron powder to the polyvinyl pyrrolidone aqueous solution is (1.5-2.5):1; the volume concentration of the polyvinyl pyrrolidone aqueous solution is 3%-7%.

[0014] Furthermore, the mass ratio of the aniline monomer to the nitrided carbonyl iron powder is (0.15-0.25):1.

[0015] A seawater corrosion-resistant wave-absorbing material with surface nitridation treatment is prepared by the above preparation method.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention abandons the complex chemical reaction and high temperature treatment requirements in the traditional method, adopts a more direct and efficient surface nitridation treatment method, and greatly simplifies the production process. This not only reduces the operation steps, but also reduces the requirements for environmental conditions. By reducing unnecessary process steps and avoiding the use of expensive equipment or materials, the present invention achieves effective control of production costs. Compared with the prior art, this method can significantly reduce resource consumption and energy use in the manufacturing process, thereby significantly reducing the overall production cost. After surface nitridation treatment, a dense iron nitride protective layer will be formed on the surface of the carbonyl iron powder. This protective layer effectively prevents the penetration of chloride ions in seawater and enhances the corrosion resistance of the material in the marine environment. The problem that traditional absorbers are difficult to achieve high wave absorption performance and good corrosion resistance at the same time is solved. The carbonyl iron powder after nitridation treatment of the present invention not only improves its corrosion resistance, but also optimizes the electromagnetic properties. The core-shell structure composite material formed improves thermal stability and effectively suppresses eddy current loss, so that the electromagnetic wave absorption efficiency of the material is significantly improved. The carbonyl iron powder prepared by the present invention has stronger durability and reliability, and is particularly suitable for long-term exposure to harsh environments such as seawater, which is crucial for the application of absorbing materials that need to maintain high performance under extreme conditions.

[0017] In summary, the surface nitriding treatment method provided by the present invention not only simplifies the production process and reduces the production cost, but more importantly, significantly improves the corrosion resistance and electromagnetic properties of the product, providing strong support for technological innovation and development in related fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 This is the distribution diagram of nitrogen element in the sample obtained in Example 1 of the present invention.

[0020] Figure 2 This is the distribution diagram of the iron element in the sample obtained in Example 1 of the present invention.

[0021] Figure 3 This is a microscopic morphology of the sample obtained in Example 1 of the present invention.

[0022] Figure 4 This is the XRD diagram of the sample obtained in Example 2 of the present invention.

[0023] Figure 5This is a comparison chart of the microwave absorption performance of the sample obtained in Example 3 of the present invention before and after corrosion.

[0024] Figure 6 This is a comparison chart of the microwave absorption performance test of the coating prepared with untreated carbonyl iron powder before and after seawater corrosion. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Seawater corrosion is different from corrosion in conventional environments. It is characterized by the coexistence of high salinity, high conductivity and high chloride ion concentration. These conditions together accelerate the corrosion process of metal materials. Chloride ions, as the main corrosion factor, can destroy the natural oxide film protective layer formed on the metal surface, thereby causing local corrosion phenomena such as pitting or intergranular corrosion. In addition, sulfate-reducing bacteria and other oxidants contained in seawater also pose additional corrosion threats to metal materials. This embodiment chooses to nitride the carbonyl iron powder; the nitride coating can spontaneously form a dense and uniform passivation film on the metal surface, with high hardness and excellent wear and corrosion resistance. This self-assembled nitride film can not only be generated rapidly under normal pressure seawater environment, but also provides an excellent barrier effect, effectively preventing the penetration of corrosive media such as chloride ions and other corrosive substances, ensuring that the carbonyl iron powder maintains the stability and reliability of its electromagnetic wave absorption performance in the marine environment for a long time.

[0027] The surface nitridation treated corrosion resistant carbonyl iron powder absorbing material prepared in the example of this embodiment is specifically realized by the following steps: S1. Surface cleaning of carbonyl iron powder, including pickling and water washing, to remove oxides and impurities on the surface; S101. Place carbonyl iron powder with an average particle size of 20 to 50 microns in a dilute hydrochloric acid solution or dilute sulfuric acid with a mass concentration of 8 to 10%, and soak it at room temperature for 5 to 10 minutes to remove oxides and impurities on the surface. After pickling, wash the carbonyl iron powder with deionized water for 3 to 4 times, each time for 2 to 3 minutes, to ensure that the surface is clean; S102, drying the cleaned carbonyl iron powder at 80-100° C. for 30-45 minutes to ensure that the surface of the carbonyl iron powder is dry and free of moisture.

[0028] The high specific surface area and special electromagnetic properties of carbonyl iron powder make it suitable for the preparation of electromagnetic wave absorbing materials. The acid pickling treatment is mainly to remove the oxide layer and other impurities that may exist on its surface, so as to improve its magnetic properties and electrical conductivity, reduce the erosion of corrosive media, and improve the corrosion resistance of the material. This is very critical for its application in magnetic materials. Carbonyl iron powder easily absorbs oxygen and water in the air, resulting in particle agglomeration. Acid pickling can reduce this agglomeration phenomenon, thereby improving its fluidity and dispersibility in the application. Carbonyl iron powder that has not been acid-washed may perform poorly in some applications due to problems such as decreased purity, unstable performance, easy agglomeration, and decreased corrosion resistance. Studies have shown that the oxidation starting temperature of the coated carbonyl iron powder has been significantly increased by washing it with deionized water during the preparation process, showing excellent thermal stability.

[0029] This embodiment uses a dilute hydrochloric acid solution with a mass concentration of 8-10% to avoid over-corrosion or incomplete pickling, avoid hydrogen embrittlement, and complete the pickling process efficiently. This embodiment determines the drying process parameters of drying at 80-100°C for 30-45 minutes through a large number of experiments. Too high a temperature and too long a time will cause the surface of the carbonyl iron powder to oxidize and form an oxide layer, thereby affecting the magnetic properties and wave absorption properties of the carbonyl iron powder. Excessive temperature will cause the particle size of the carbonyl iron powder to change, affecting its application performance, and will also destroy the microstructure of the carbonyl iron powder, such as the "onion skin" structure, thereby affecting its magnetic properties. However, the drying temperature and time are too low, and the moisture and solvent in the carbonyl iron powder cannot be effectively removed, resulting in insufficient product purity. Although low-temperature drying can reduce the risk of damage to the structure of the carbonyl iron powder, it will prolong the drying time and cause energy waste.

[0030] S2. The pretreated carbonyl iron powder is subjected to nitriding treatment in a high-temperature nitriding furnace, and the nitriding temperature and time are controlled to form a uniform and dense nitride layer on the surface of the carbonyl iron powder.

[0031] In some specific embodiments, the specific process of S2 is to spread the carbonyl iron powder pretreated by S1 into the nitriding furnace, and fill the nitriding furnace with one of nitrogen or ammonia, and make the gas purity at 99.9% to ensure the nitriding effect.

[0032] In some possible implementations, the nitriding temperature of the nitriding treatment is 400-600° C., and the nitriding time is 4-8 hours. During the nitriding process, the nitriding gas is continuously introduced, and the nitrogen reacts with the surface of the carbonyl iron powder to form a uniform nitride oxide layer. By controlling the temperature and time, the thickness of the nitride layer reaches 1-3 microns.

[0033] In this embodiment, in order to ensure the smooth progress of the reaction and form a uniform nitrogen oxide layer, thermodynamic and kinetic conditions must be met at the same time. For carbonyl iron powder, the temperature distribution in the nitriding furnace is uniform, whether it is the upper surface or the lower surface, so the thermodynamic conditions are consistent at all reaction sites. From a kinetic point of view, the reaction rate depends on factors such as the concentration of reactants, the presence or absence of a catalyst, and the contact area. In this embodiment, the uniformity of the gas concentration in the entire reaction environment is ensured by continuously introducing an excess of reaction gas into the nitriding furnace. Since the gas phase material has a higher fluidity than the solid iron powder, this allows the reaction gas molecules to fully contact and surround the carbonyl iron powder particles, whether on the upper surface or the lower surface of the carbonyl iron powder, thereby ensuring the same kinetic conditions. This effective control of the gas environment ensures that nitrogen and the surface of the carbonyl iron powder can undergo a uniform nitriding reaction, ultimately achieving the overall consistency of the material and the high efficiency of the reaction. In summary, by maintaining the consistency of the temperature in the nitriding furnace and maintaining a continuous and sufficient supply of reaction gas, it can be ensured that during the nitriding reaction, all surfaces of the carbonyl iron powder are under the same thermodynamic and kinetic conditions, thereby ensuring the uniformity and consistency of the nitriding reaction.

[0034] In some possible implementations, after nitridation is completed, the carbonyl iron powder in the nitridation furnace is slowly cooled to room temperature to avoid cracking of the nitrided layer caused by rapid cooling.

[0035] In this embodiment, the nitride has excellent corrosion resistance and wear resistance, and has little effect on the magnetic and electromagnetic properties of the material. In this embodiment, ammonia or nitrogen is used as the atmosphere medium, and the atmosphere is heated to a predetermined temperature by a heating device. The carbonyl iron powder is placed in a temperature-controlled atmosphere. After a certain period of time, the surface of the carbonyl iron powder reacts with the gas in the atmosphere to form a nitride layer.

[0036] In this embodiment, when ammonia is used as the atmosphere medium, since ammonia is easy to decompose under certain conditions, the decomposed active nitrogen atoms are adsorbed on the carbonyl surface and then diffuse from the surface to the inside to form a nitride layer. The decomposition rate of ammonia increases with the increase of temperature. In the temperature range of 400~600℃, the natural decomposition rate of ammonia can tend to be completely decomposed. Nitrogen atoms diffuse inward from the surface of carbonyl iron powder to form a nitride layer of a certain thickness. At the nitriding temperature, the active nitrogen atoms in the activated layer of carbonyl iron powder adsorbed with nitrogen atoms move to the inside of the iron metal lattice to form nitrides, and produce a certain nitride concentration gradient to enhance the bonding strength between the nitride layer and the carbonyl iron powder.

[0037] After nitriding is completed, ensure that the furnace temperature naturally drops to a safe range. When the furnace temperature drops below 100°C, air or nitrogen can be introduced and the furnace cover can be opened for natural cooling.

[0038] S3. Surface treatment is performed on the carbonyl iron powder after nitriding to improve the stability and corrosion resistance of the nitriding layer.

[0039] S301, heat-treating the nitrided carbonyl iron powder in a vacuum drying oven at 80-100° C. for 1-2 hours, maintaining the vacuum degree at no higher than -0.1 MPa, to ensure stable bonding between the nitrided layer and the carbonyl iron powder.

[0040] In order to increase the bonding strength between the nitride layer and the carbonyl iron powder matrix, the present embodiment continues to post-treat the nitrided carbonyl iron powder in a vacuum drying oven. The post-treated nitrided carbonyl iron powder can maintain stability for a longer time in a seawater environment. The present embodiment continues to heat treat at 80-100°C for 1-2 hours in a vacuum drying oven, which can improve the bonding strength between the nitride layer and the carbonyl iron powder matrix and improve its stability in a marine environment.

[0041] S302, using polyaniline to modify the surface of the nitrided carbonyl iron powder treated in S301.

[0042] Add nitrided carbonyl iron powder to polyvinyl pyrrolidone (PVP) aqueous solution and oscillate with ultrasonic for 0.4-0.6 h. The mass ratio of nitrided carbonyl iron powder to PVP is 1.5-2.5:1, and the volume concentration of PVP aqueous solution is 3-7%.

[0043] Then, aniline monomer is added to the mixed solution, the mass ratio of aniline monomer to nitrided carbonyl iron powder is 0.15-0.25:1, and pre-stirred with a glass rod for 10-12 minutes. Then, the solution is magnetically stirred in an ice bath for 2-3 hours to obtain a nitrided carbonyl iron powder / polyaniline composite absorbent. Finally, it is washed with anhydrous ethanol and deionized water for 2-3 minutes.

[0044] In this embodiment, polyaniline (PANI) is coated on the nitrided carbonyl iron powder to further enhance its anti-corrosion performance. The modified carbonyl iron powder has strong hydrophobicity, and the static water contact angle can reach 141°. After being immersed in a sodium chloride solution for 240 hours, the modified carbonyl iron powder still exhibits strong electromagnetic absorption performance.

[0045] The polyaniline described in this embodiment has good electrical conductivity and environmental stability. This embodiment is to polymerize aniline monomer in situ on the surface of nitrided carbonyl iron powder to form polyaniline; polyaniline is used to modify the surface of the nitrided carbonyl iron powder to enhance hydrophobicity and corrosion resistance. Polyaniline has good chemical stability and can form a protective layer on the surface of the carbonyl iron powder to reduce the contact between the corrosive medium and the iron powder and improve corrosion resistance. Improve electromagnetic properties. The conductive properties of polyaniline can be combined with the magnetic properties of the carbonyl iron powder to improve the electromagnetic properties of the carbonyl iron powder composite material, such as improving magnetic permeability and reducing hysteresis loss. Improve wear resistance: polyaniline has a high hardness and can form a wear-resistant layer on the surface of the carbonyl iron powder to reduce the wear of the powder during processing and use. Enhance adhesion: polyaniline has strong adhesion to the metal surface, which can improve the dispersibility and interfacial bonding of carbonyl iron powder in the composite material. Environmental stability: polyaniline can maintain good stability under different environmental conditions, which helps to improve the application performance of carbonyl iron powder in complex environments. Adjustable performance: The doping degree of polyaniline can be adjusted by changing the polymerization conditions, thereby achieving customized modification of the surface properties of carbonyl iron powder. Compared with other expensive surface modification materials, the use of monomer aniline is relatively low cost, which helps to reduce the overall production cost.

[0046] Example 1 S1. Select carbonyl iron powder with an average particle size of 20-50 microns and a purity of not less than 99.5%, which is suitable for the substrate of electromagnetic wave absorbing materials. Place the carbonyl iron powder in a dilute hydrochloric acid solution with a mass concentration of 8% and soak it at room temperature for 5 minutes to remove surface oxides and impurities. After pickling, use deionized water to wash the carbonyl iron powder 3 times, 2 minutes each time, to ensure the surface is clean. Then dry the washed carbonyl iron powder at 80°C for 30 min; S2. Spread the carbonyl iron powder evenly in the nitriding furnace; continuously introduce ammonia gas into the nitriding furnace and control the gas purity to be above 99.9% to ensure the nitriding effect; nitriding is performed at 400°C for 4 h; after nitriding, the carbonyl iron powder is naturally cooled to room temperature.

[0047] S3. Heat-treat the cooled carbonyl iron nitride powder in a vacuum drying oven at 80°C for 1 hour. The vacuum degree of the vacuum drying oven is not higher than -0.1 MPa to ensure the stability of the nitride layer. Then add the carbonyl iron nitride powder to a 3% volume concentration PVP aqueous solution and ultrasonically oscillate for 0.4 h; then add aniline monomer, stir with a glass rod for 10 min, and then magnetically stir the solution in an ice bath for 2 h; finally, wash it twice with anhydrous ethanol and deionized water.

[0048] The mass ratio of the nitrided carbonyl iron powder to the polyvinyl pyrrolidone aqueous solution is 1.5:1; the mass ratio of the aniline monomer to the nitrided carbonyl iron powder is 0.15:1.

[0049] Example 2 S1. Select carbonyl iron powder with an average particle size of 20-50 microns and a purity of not less than 99.5%, which is suitable for the substrate of electromagnetic wave absorbing materials. Place the carbonyl iron powder in a 9% dilute hydrochloric acid solution and soak it at room temperature for 7 minutes to remove surface oxides and impurities. After pickling, use deionized water to wash the carbonyl iron powder 4 times, 3 minutes each time, to ensure the surface is clean. Then dry the washed carbonyl iron powder at 90°C for 35 minutes; S2. Spread the carbonyl iron powder evenly in the nitriding furnace; continuously introduce nitrogen into the nitriding furnace and control the gas purity to be above 99.9% to ensure the nitriding effect; nitriding is performed at 500°C for 6 h; after the nitriding is completed, the carbonyl iron powder is naturally cooled to room temperature.

[0050] S3. Heat-treat the cooled carbonyl iron nitride powder in a vacuum drying oven at 90°C for 1.5 hours. The vacuum degree of the vacuum drying oven is not higher than -0.1 MPa to ensure the stability of the nitride layer. Then add the carbonyl iron nitride powder to a 5% volume concentration PVP aqueous solution and ultrasonically oscillate for 0.5 h. Then add aniline monomer and stir with a glass rod for 11 min. Then, magnetically stir the solution in an ice bath for 2.5 h. Finally, wash it three times with anhydrous ethanol and deionized water.

[0051] The mass ratio of the nitrided carbonyl iron powder to the polyvinyl pyrrolidone aqueous solution is 2:1; the mass ratio of the aniline monomer to the nitrided carbonyl iron powder is 0.2:1.

[0052] Example 3 S1. Select carbonyl iron powder with an average particle size of 20-50 microns and a purity of not less than 99.5%, which is suitable for the substrate of electromagnetic wave absorbing materials. Place the carbonyl iron powder in a 10% dilute hydrochloric acid solution and soak it at room temperature for 8 minutes to remove surface oxides and impurities. After pickling, use deionized water to wash the carbonyl iron powder 3 times, 2 minutes each time, to ensure the surface is clean. Then dry the washed carbonyl iron powder at 100°C for 40 min; S2. Spread the carbonyl iron powder evenly in the nitriding furnace; continuously introduce nitrogen into the nitriding furnace and control the gas purity to be above 99.9% to ensure the nitriding effect; nitriding is performed at 600°C for 8 h; after nitriding, the carbonyl iron powder is naturally cooled to room temperature.

[0053] S3. Heat-treat the cooled carbonyl iron nitride powder in a vacuum oven at 100°C for 2 hours. The vacuum degree of the vacuum oven is not higher than -0.1 MPa to ensure the stability of the nitride layer. Then add the carbonyl iron nitride powder to a 7% volume concentration PVP aqueous solution and ultrasonically oscillate for 0.6 h; then add aniline monomer, stir with a glass rod for 12 min, and then magnetically stir the solution in an ice bath for 3 hours; finally, wash it three times with anhydrous ethanol and deionized water.

[0054] The mass ratio of the nitrided carbonyl iron powder to the polyvinyl pyrrolidone aqueous solution is 2.5:1; the mass ratio of the aniline monomer to the nitrided carbonyl iron powder is 0.25:1.

[0055] Example 4 S1. Select carbonyl iron powder with an average particle size of 20-50 microns and a purity of not less than 99.5%, which is suitable for the substrate of electromagnetic wave absorbing materials. Place the carbonyl iron powder in a 10% dilute sulfuric acid solution and soak it at room temperature for 10 minutes to remove surface oxides and impurities. After pickling, use deionized water to wash the carbonyl iron powder 4 times, 2 minutes each time, to ensure the surface is clean. Then dry the washed carbonyl iron powder at 90°C for 45 minutes; S2. Spread the carbonyl iron powder evenly in the nitriding furnace; continuously introduce ammonia into the nitriding furnace and control the gas purity to be above 99.9% to ensure the nitriding effect; nitriding at 400°C for 8 h; after nitriding, naturally cool the carbonyl iron powder to room temperature.

[0056] S3. Heat-treat the cooled carbonyl iron nitride powder in a vacuum drying oven at 80°C for 1 hour. The vacuum degree of the vacuum drying oven is not higher than -0.1 MPa to ensure the stability of the nitride layer. Then add the carbonyl iron nitride powder to a 5% volume concentration PVP aqueous solution and ultrasonically oscillate for 0.5 h; then add aniline monomer, stir with a glass rod for 11 min, and then magnetically stir the solution in an ice bath for 2.5 h; finally, wash it three times with anhydrous ethanol and deionized water.

[0057] The mass ratio of the nitrided carbonyl iron powder to the polyvinyl pyrrolidone aqueous solution is 2:1; the mass ratio of the aniline monomer to the nitrided carbonyl iron powder is 0.2:1.

[0058] Comparative Example 1 In S1, the carbonyl iron powder is washed with deionized water only 4 times, each time for 3 minutes; then the washed carbonyl iron powder is dried at 90° C. for 35 minutes; hydrochloric acid is not used for pickling; and the remaining steps are the same as those in Example 2.

[0059] Comparative Example 2 The carbonyl iron powder after washing in S1 is dried at 200° C. for 35 min; the remaining steps are the same as those in Example 2.

[0060] Comparative Example 3 The carbonyl iron powder washed in S1 was dried at 40° C. for 35 min; the remaining steps were the same as those in Example 2.

[0061] Comparative Example 4 In S2, the nitriding temperature is 800° C. and the nitriding time is 3 h; the remaining steps are the same as those in Example 2.

[0062] Comparative Example 5 In S2, the nitriding temperature is 300° C. and the nitriding time is 10 h; the remaining steps are the same as those in Example 2.

[0063] Comparative Example 6 In S2, the nitriding temperature is 300° C. and the nitriding time is 3 h; the remaining steps are the same as those in Example 2.

[0064] Comparative Example 7 In S2, the nitriding temperature is 800° C. and the nitriding time is 10 h; the remaining steps are the same as those in Example 2.

[0065] Comparative Example 8 The heat treatment temperature in S3 is 150°C, and the remaining steps are the same as in Example 2.

[0066] Comparative Example 9 No heat treatment is performed in S3, and the remaining steps are the same as in Example 2.

[0067] Comparative Example 10 After the heat treatment in S3, no subsequent surface modification step is performed, and the remaining steps are the same as in Example 2.

[0068] The performance comparison between the embodiment of this embodiment and the comparative example is shown in Table 1: Table 1 Comparison of electromagnetic parameters of various embodiments and comparative examples before and after corrosion In order to more clearly illustrate the embodiments of the present invention, Figure 1 is the element distribution diagram of nitrogen element of the sample obtained in Example 1, Figure 2 is the element distribution diagram of the iron element of the sample obtained in Example 1, from Figure 1 and Figure 2 It can be seen that in the sample obtained in Example 1, the nitrogen element is evenly distributed on the surface of the carbonyl iron powder. Figure 3 This is a microscopic morphology of the corrosion-resistant carbonyl iron powder obtained in Example 1. Figure 4 The XRD spectrum of the carbonyl iron powder after nitridation obtained in Example 2 shows Fe4N 0.94 Combining the microstructure and XRD spectrum, it can be seen that the outer surface of the carbonyl iron powder is covered with a uniform, dense and continuous iron nitride layer. Figure 5 The microwave absorption performance test comparison of the coating prepared for the sample of Example 3 before and after seawater corrosion shows that the microwave absorption performance of the sample before and after corrosion has hardly changed, only decreasing from 6.8 GHz to 6.3 GHz, a decrease of only 7.35%. Figure 6 The comparison of the microwave absorption performance of the coating prepared by untreated carbonyl iron powder before and after seawater corrosion shows that the effective absorption bandwidth of the untreated carbonyl iron powder is reduced to 0 after seawater corrosion. Figure 5 and Figure 6 By comparison, it can be seen that the carbonyl iron powder prepared by the present invention has excellent corrosion resistance.

[0069] Table 1 is a comparison of the effective absorption bandwidth of the present embodiment, the comparative example, the untreated carbonyl iron powder and other existing treatment methods under the actual seawater corrosion environment. Through nitridation and surface modification, the corrosion resistance and microwave absorption performance of the carbonyl iron powder are effectively improved.

[0070] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.

[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A method for preparing a seawater corrosion resistant absorbing material with surface nitridation treatment, characterized in that: The specific steps are as follows: S1. Pre-treating the carbonyl iron powder, including pickling and water washing; S2, performing surface nitriding treatment on the pretreated carbonyl iron powder; S3. heat treating and surface modifying the carbonyl iron powder after nitriding.

2. The method for preparing a surface nitrided seawater corrosion resistant absorbing material according to claim 1, characterized in that: The specific steps of S1 are: S101. Soak carbonyl iron powder with an average particle size of 20-50 μm in a dilute hydrochloric acid or dilute sulfuric acid solution with a mass concentration of 8%-10% for 5-10 minutes; then wash with deionized water for 3-4 times, each time for 2-3 minutes; S102, drying the cleaned carbonyl iron powder at 80-100°C for 30-45 min.

3. The method for preparing a seawater corrosion resistant absorbing material with surface nitridation treatment according to claim 1, characterized in that: The specific process of S2 is: continuously filling the nitriding furnace with nitriding gas until the furnace body is full, and then spreading the carbonyl iron powder treated by S1 into the nitriding furnace for nitriding at 400-600° C. for 4-8 h; and then naturally cooling to room temperature.

4. The method for preparing a surface nitrided seawater corrosion resistant absorbing material according to claim 3, characterized in that: The nitriding gas is one of nitrogen and ammonia.

5. The method for preparing a surface nitrided seawater corrosion resistant absorbing material according to claim 1, characterized in that: The heat treatment in S3 is specifically heat treatment at 80-100° C. for 1-2 h in a vacuum drying oven with a vacuum degree not higher than -0.1 MPa.

6. The method for preparing a surface nitrided seawater corrosion resistant absorbing material according to claim 1, characterized in that: The specific process of surface modification in S3 is as follows: adding the heat-treated nitrided carbonyl iron powder to a polyvinyl pyrrolidone aqueous solution, ultrasonically oscillating for 0.4 to 0.6 h, adding aniline monomer, stirring with a glass rod for 10 to 12 min, and then magnetically stirring the solution in an ice bath for 2 to 3 h; finally, washing with anhydrous ethanol and deionized water for 2 to 3 times respectively.

7. The method for preparing a surface nitrided seawater corrosion resistant absorbing material according to claim 6, characterized in that: The mass ratio of the nitrided carbonyl iron powder to the polyvinyl pyrrolidone aqueous solution is (1.5-2.5):1; the volume concentration of the polyvinyl pyrrolidone aqueous solution is 3%-7%.

8. The method for preparing a surface nitrided seawater corrosion resistant absorbing material according to claim 6, characterized in that: The mass ratio of the aniline monomer to the nitrided carbonyl iron powder is (0.15-0.25):

1.

9. A seawater corrosion resistant absorbing material with surface nitridation treatment, prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • A method for preparing an aluminum phosphate-coated carbonyl iron antioxidant microwave absorbing material

    CN107253738B

  • Rust-resistant carbonyl iron powder wave-absorbing material and preparation method thereof

    CN113388231A